Older caregivers’ responsibilities and strategies for their cohabiting partners living at home—a qualitative systematic literature review - Glasdam, Stinne; Xu, Hongxuan; Slåtsveen, Ruth-Ellen; Stilwell, Christie; Wind, Gitte; Gulestø, Ragnhild Julante Andersen; Turcotte, Pier-Luc (Frontiers in Public Health, 2025)
BackgroundAgeing-in-place policies have increasingly shifted elder care responsibilities onto family members. Among older cohabiting couples, one’s partner’s illness significantly impacts the other’s daily life and well-being.AimTo explore the responsibilities and strategies of caregiving partners in older cohabiting couples from the perspectives of cohabiting caregivers.MethodsA qualitative systematic literature review was conducted across seven databases, following PRISMA guidelines and registered in PROSPERO (CRD42025632103). Sixty-five studies were included based on predefined inclusion and exclusion criteria using Covidence. Quality was assessed using the Critical Appraisal Skills Programme (CASP) checklist for qualitative studies. Data were synthesised through descriptive numerical summaries and thematic analysis.ResultsThe studies, conducted in 20 countries, primarily used individual interviews for data collection. Three overarching themes emerged: (1) strategies directed towards the partner, (2) strategies to maintain personal identity and space, and (3) strategies for navigating formal care systems. Cohabiting caregivers often assumed daily responsibilities despite emotional and physical strain. They relied on both informal and formal support to care for their partner and preserve time for themselves. However, formal care involvement led to issues such as broken agreements and inadequate services.ConclusionOlder cohabiting caregivers constantly balance and adapt their caregiving roles in relation to their partner, themselves, and formal care providers. This shift in responsibility results in an often invisible, morally-driven labour that remains under-recognised in Ageing-in-place policies. The study highlights the need for policy frameworks and interventions that acknowledge caregivers’ moral labour, enhance the quality of formal care, and support caregiver autonomy.Clinical trial registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025632103, identifier (CRD42025632103).